2016
DOI: 10.1590/1809-2950/16115523032016
|View full text |Cite
|
Sign up to set email alerts
|

O fisioterapeuta do estado de São Paulo

Abstract: | To identify the profile of the physical therapist is important for a profession overview, which can help organs and institutions of higher education to train more qualified, fulfilled, valued, and recognized professionals for health care. The profile of the physical therapist has already been studied in other states, specific specialties or workplace; however we are not aware of the current profile of the physical therapist in the state of São Paulo (SP). The aim of this study was to describe the profile of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 13 publications
0
4
0
7
Order By: Relevance
“…Most of professionals still work on secondary and tertiary care, which results from the profession's history; however, a significant number already works on primary care, which is being more recently developed and encouraged by public policies 29 . The fact that most professionals have more than one job and work more than 8 hours a day is also observed in a study with physical therapists from Londrina/ 12,13,31 . Having most of the professionals who answered the survey being self-employed and working at private institutions reaffirms a study performed throughout Brazil that shows that 60% of physical therapists' registries in the National Registry of Health Facilities (CNES) are from private area, given that, in the country's southern region, this value leaps to 76.3%, which confirms the private healing rehabilitation profile of physical therapists previously described in literature 24 .…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Most of professionals still work on secondary and tertiary care, which results from the profession's history; however, a significant number already works on primary care, which is being more recently developed and encouraged by public policies 29 . The fact that most professionals have more than one job and work more than 8 hours a day is also observed in a study with physical therapists from Londrina/ 12,13,31 . Having most of the professionals who answered the survey being self-employed and working at private institutions reaffirms a study performed throughout Brazil that shows that 60% of physical therapists' registries in the National Registry of Health Facilities (CNES) are from private area, given that, in the country's southern region, this value leaps to 76.3%, which confirms the private healing rehabilitation profile of physical therapists previously described in literature 24 .…”
Section: Discussionmentioning
confidence: 59%
“…However, this recent expansion in the specializations can also be related to the implementation of multi-professional residencies in health and a bigger implementation of specialization programs 27 . The majority of physical therapists (73.5%) chose to take specialization courses, this number is even higher in the State of São Paulo, having 87.7% of professional with any specialization 12 and it is smaller in Santa Catarina, where 52.6% of professionals have a specialization 13 . Although the research shows the low number of master's and PhD professionals, a growth is observed in the last ten years, accomplishing one of the profession's great challenges, which is the education of new researchers and knowledge progress and development 28 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Este estudo mostrou a predominância de mulheres bacharelandas em fisioterapia. Esta porcentagem está de acordo com os outros estudos que verificaram a predominância de mulheres Fisioterapeutas (SHIWA et al, 2016;VIANA et al, 2012;BADARÓ;GUILHEM, 2011;NOZAWA et al, 2008;TRELHA et al, 2003).…”
Section: Resultsunclassified